A Novelty Once Methode Power System Policies Based On SCS (Solar Cell System) - Radiyan Rahim (International Conference of ASEAN Prespective and Policy (ICAP), 2018)
The Working Principle Of Solar Cells Is Very Simple. Solar Cells Are An Energy Conversion Tool That Transforms Solar Energy For Electrical Energy. Energy From Sunshine Accommodated Then Converted into Electrical Energy. Such Energy Can Be Used For Running Various Kinds Of Electronic Devices Starting From Lighting Lights, Moving Motor, And Many More Others. The following article is the effort that must be done to make solar energy as an alternative energy in overcoming the needs of household electricity in the village of Pardamean Dusun Gunung Tua Kec.Pahae Jae Kab. North Tapanuli North Prov.Sumatera Far Inside With Difficult Access And Unspoiled Electricity PLN.